Taiwan a new history (An East Gate book, 2015)
Since its initial publication in 1999, Taiwan: A New History has established itself as the book of choice on the history of Taiwan. Conceived as a cohesive and interconnected set of interpretive and narrative essays, it is the most integrated, comprehensive, and accessible history of Taiwan published in any Western language. The contributors are the very best people in their specialties, drawn from North America, Europe, and Asia. This new edition expands the coverage from where the first edition ended in 1995 to 2006. It includes new material on democratization, party politics, and the independence movement. Collectively, the chapters take the reader from the geographical and climatological setting, through the stages of premodern history and contact with China and the West, through the Japanese occupation, to the successful establishment of a modern state.